Hubungan Pola Konsumsi Zat Besi Dan Kepatuhan Mengkonsumsi Tablet Fe Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Sambung Makmur Tahun 2015 - Yuliana Salman; Ideris Ideris; Siti Maryam Muharramah; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2016)
Data of Riskesdas 2013, prevalence of anemia in pregnant women in Indonesia is 37,1%. Based on a preliminary survey of Banjar health districts in 2014, Mean of prevalence anemia in pregnant women from 23 health center are 10.82%. And the highest is in the Sambung Makmur health center is 28.06%. This research aims to know the correlation of the pattern consumption of iron and consume Fe tablets compliance with the incidence of anemia in pregnant women in Sambung Makmur health center 2015. This research used analytic survey with cross sectional approach. This research conducted on 43 pregnant women respondents. Based on statistic test on multiple variables by using the chi-square show that iron consumption the pattern p value = 0.003 and compliance to consume Fe tablets p value = 0.001 that means there is a significant correlation between consumption patterns and compliance to consume Fe tablets with anemia. Suggested to the health centers to provide counseling about the consumption the both iron and tablets Fe to avoid the incidence of anemia in pregnant women.